'SENitizing' migrant children in inclusive settings: exploring the impact of the Salamanca Statement thinking in Italy and the United States. Issue 7 (3rd August 2019) - Migliarini, Valentina; Stinson, Chelsea; D'Alessio, Simona
ABSTRACT: This paper emphasizes the aporetic nature of the Salamanca Statement on Special Needs Education (UNESCO, 1994), adopting a cross-cultural perspective. It draws on an intersectional perspective on inclusion (Connor, Ferri & Annamma, 2016; Artiles & Kozleski, 2016 ; Erevelles, 2014) to argue that although inclusion has been defined by such an international declaration as a transformative project to ensure access to quality education for all students, national inclusive policies are still focused on a pathological construction of student difference,   slowly incorporating children from different linguistic and ethnic backgrounds. The focus on Italy and the United States is a response to examine the discourses and practices of inclusion in two countries that have been impacted by the Salamanca Statement thinking. To substantiate our argument concerned with the limitations embedded in the Salamanca Statement, data from two empirical studies conducted in Rome and in Upstate New York will be presented. The studies show how inclusion leads to overrepresentation of migrant students in Special Educational Needs. We conclude that the Salamanca Statement has been transferred into a tool to strengthen normality against difference, and that it should focus on interrupting micro-exclusions for groups sitting at the intersections of race, ability and other identity markers.